Prediction of change in suitable habitats of Senna obtusifolia and Senna tora under climate change - Yineng Chen; Chenlu Luo; Xue Huang; Wenjie Li; Han Yan; Huiyue Ji; Jiayu Zhou; Hai Liao (Scientific Reports)
Abstract Senna obtusifolia (L.) Irwin & Barneby and Senna tora (L.) Roxb represent important medicinal resources in traditional Chinese medicine for more than two millennia. Sustainable resource utilization and preservation strategies for Senna species necessitate a thorough understanding of the climatic factors governing their distribution patterns. Therefore, this study aimed to identify the key climate variables shaping the current and potential future global distribution of both Senna species. To achieve this, the MaxEnt ecological niche model was employed, integrating species occurrence data with relevant environmental variables. The results indicated that Bio13 and Bio14 were the most critical variables affecting distribution of S. tora, while Bio6 and Bio14 were crucial for S. obtusifolia. The moderate and high suitability habitats of S. obtusifolia and S. tora consist of ca. 189.69 × 104 km2 and 129.07 × 104 km2, respectively, under current situation. Moreover, the global distribution of both species under various climate scenarios revealed that the suitable habitats of both Senna species will reach the maximum during the 2081–2100 period under the SSP585 scenario. Projections across all four climate scenarios indicate a general northward migration in the core distribution of both Senna species. Intriguingly, the observed high degree of ecological niche overlap between the two species aligns with their close phylogenetic relationship. These findings provide valuable insights into the potential future distribution and ecological niche of Senna species, informing sustainable utilization and preservation strategies for Senna resources.